Surplus Free Cash Flow, Stock Market Segmentations, And Earnings Management: The Case Of Jordan - Toumeh, Ahmad Adnan Hussein (2020)
The current study provides evidence concerning the influence of surplus free cash flow and stock market segmentations on income-increasing earnings management practices in Jordan. As well, the study identifies the effect of audit quality and an independent audit committee as moderating variables on those relationships. The sample of the study used all non-financial companies that were listed on the Amman Stock Exchange for the period spanning from 2013 to 2017. Panel data analysis was employed to answer the research questions and accomplish the objectives of the study. The analyses includes several statistical techniques such as descriptive statistics, univariate analysis, and multivariate analysis. However, the robust standard errors for pooled OLS regression were used as the primary statistical tool for this study. The results found a significant and positive relationship between earnings management and surplus free cash flow. As well, the results provided conclusive evidence that the stock market segmentation was significantly and positively associated with earnings management. In addition, the study showed that the moderating role of audit quality weakens the association between surplus free cash flow, stock market segmentations, and earnings management. The moderating role of the independent audit committee weakens the association between stock market segmentations and earnings management. Simultaneously, it has no significant effect on the association between earnings management and surplus free cash flow. This research adds value to scholarship by investigating the stock market segmentations variable.Further, this is the initial empirical attempt to investigate the impact of surplus free cash flow on earnings management in Jordan. The study provides meaningful information for companies seeking to understand and reduce agency problems in the Jordanian context. Also, the results of the study will provide beneficial information to investors, regulators, external auditors, policymakers, and shareholders.